2007
DOI: 10.1103/physreve.75.056401
|View full text |Cite
|
Sign up to set email alerts
|

Emittance growth mechanisms for laser-accelerated proton beams

Abstract: In recent experiments the transverse normalized rms emittance of laser-accelerated MeV ion beams was found to be < 0.002 mm mrad, which is at least 100 times smaller than the emittance of thermal ion sources used in accelerators [T. E. Cowan, Phys. Rev. Lett. 92, 204801 (2004)]. We investigate the origin for the low emittance of laser-accelerated proton beams by studying several candidates for emittance-growth mechanisms. As our main tools, we use analytical models and one- and two-dimensional particle-in-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Furthermore, dynamic control of mega-ampere electron currents in metals using ionization-driven resistive magnetic fields has been proposed by Sentoku et al, 15 and collimation, hollowing, or filamentation of the electron beams have been found in experiments and simulations. Kemp et al 16 investigated the origin for the low emittance of laser-accelerated proton beams and found that the dominant source is filamentation of the laser-generated hot electron jets that drive the ion acceleration. Recently, hybrid and particle-in-cell (PIC) methods have been used to study resistivity effects on the behavior of the hot electron transport through different target materials [17][18][19][20] or density gradients, 21 and their effect on proton acceleration at the target rear side.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, dynamic control of mega-ampere electron currents in metals using ionization-driven resistive magnetic fields has been proposed by Sentoku et al, 15 and collimation, hollowing, or filamentation of the electron beams have been found in experiments and simulations. Kemp et al 16 investigated the origin for the low emittance of laser-accelerated proton beams and found that the dominant source is filamentation of the laser-generated hot electron jets that drive the ion acceleration. Recently, hybrid and particle-in-cell (PIC) methods have been used to study resistivity effects on the behavior of the hot electron transport through different target materials [17][18][19][20] or density gradients, 21 and their effect on proton acceleration at the target rear side.…”
Section: Introductionmentioning
confidence: 99%
“…The rear-surface acceleration ͑RSA͒ ϳTV/ m electric field ionizes atoms and accelerates ions ͑that expand together with the electrons in a quasineutral beam͒ normal to the surface. 13,20 FSA produces a low-quality beam, 21 because of the stochastic nature of the laser-plasma interaction and hence of the charge separation field at the critical density interface. FSA has been clearly identified by nuclear activation 22 and neutron spectroscopy 23 techniques.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 If heating of the target is performed prior to the laser irradiation in order to eliminate the hydrogen contaminants as much as possible, the acceleration of heavier ions is favored. 39 Detailed analysis of the acceleration mechanism 39 has shown that these values are the lowest achievable values, limited by scattering of protons in magnetic filaments present on the target rear surface. As the laser is switched off, electrons cool down by adiabatic energy transfer to the ions, 37 leading to a decrease in the driving electric field.…”
Section: Introductionmentioning
confidence: 99%